Applications to Extremally Disconnected Spaces - O. Ravi, N. Rayshima, C.Rajan (Mathematical Statistician and Engineering Applications, 2022)
In this paper, the mixed and ordinary operators are characterized in the classes of rw -sets and r*w-sets. Certain topological sets that are inherited from w-open set, open set and d-open set are characterized using rw -sets and r*w-sets. More over the behavior of rw -sets and r*w-sets in Extremally Disconnected spaces are investigated. The Inclusion chains among the mixed and ordinary operators are refined in the domains of rw -sets and r*w-sets.